Present situation and future potential of cassava in Thailand - Sriroth, K.; Rojanaridpiched, Chareinsuk; Vichukit, Vichan; Uriyapan, Preecha; Oates, Christopher G. (International Center for Tropical Agriculture, 2001)
In Thailand cassava (Manihot esculenta Crantz) is considered one of the most important economic crops. Thailand has demonstrated the importance of cassava as more than a subsistence crop, and has developed a large and complex industrial system for processing and marketing of the crop. Production of cassava has steadily increased during the 1970s and 80s through expansion of the planted area, but has decreased again since the early 1990s. The national average yield has remained rather constant at about 14.5 t/ha. Major production problems are declining soil productivity, soil erosion and farmers’ poverty. Since 1959, products obtained from cassava have been a major export commodity for Thailand, assisted by relatively easy market access to the EU. In a bid to meet the increasing demand, rapid growth in the industry also led to certain weaknesses. Cassava roots are utilized for making dry chips, pellets, native starch, modified starch, MSG (monosodium glutamate), glucose, fructose, sorbitol, sago, citric acid, while starch is used in the paper, textile, and plywood industries. Of the products made from cassava, cassava starch and pellets are the only ones exported. Export companies are allocated export quotas of pellets to the EU market, but must seek new markets outside the EU to get a larger incentive quota for the EU. This helps to increase the farmers’ income and reduce poverty.